Design and Deployment of Django-based Housing Information Management System. Issue 1 (1st February 2023) - Yu, Xiya; Li, Xianhe; Wu, Changping; Xu, Gongyou
Abstract: With the further development of diversification and nationalization of the housing market, the demand of housing enterprises for digitalization and refinement of housing management is growing. The original web service system has problems of low development efficiency, long development cycle and difficulty in changing requirements, which can hardly meet the current growing and changing requirements. Based on the existing technology, we built a lightweight and agile development system based on Django framework. Based on the comprehensive study of MVC design pattern and MTV design pattern, we analyzed the requirements of the listing management system, wrote the data interaction logic using Django framework, used MySQL database and Redis, OSS, SMS and SMTP middleware. The core design of the housing information management system is optimized, unifying user login and registration behavior, fine-grained decentralization of system users, unifying front-end and back-end data exchange standards, and making dynamic back-end settings, recording behavior logs and developing multi-environment configuration optimization for the system, bringing positive contribution to the digitalization and fine-grained management of housing enterprises' listings.